Detecting Memory Impairment in Deaf People: A New Test of Verbal Learning and Memory in British Sign Language. (24th November 2016) - Denmark, Tanya; Marshall, Jane; Mummery, Cath; Roy, Penny; Woll, Bencie; Atkinson, Joanna
Abstract: Objective: Most existing tests of memory and verbal learning in adults were created for spoken languages, and are unsuitable for assessing deaf people who rely on signed languages. In response to this need for sign language measures, the British Sign Language Verbal Learning and Memory Test (BSL-VLMT) was developed. It follows the format of the English language Hopkins Verbal Learning Test Revised, using standardized video-presentation with novel stimuli and instructions wholly in British Sign Language, and no English language requirement. Method: Data were collected from 223 cognitively healthy deaf signers aged 50–89 and 12 deaf patients diagnosed with dementia. Normative data percentiles were derived for clinical use, and receiver-operating characteristic curves computed to explore the clinical potential and diagnostic sensitivity and specificity. Results: The test showed good discrimination between the normative and clinical samples, providing preliminary evidence of clinical utility for identifying learning and memory impairment in older deaf signers with neurodegeneration. Conclusions: This innovative video testing approach transforms the ability to accurately detect memory impairments in deaf people and avoids the problems of using interpreters, with international potential for adapting similar tests into other signed languages.